Pengaruh Literasi Keuangan Syariah Terhadap Inklusi Keuangan Syariah pada Pondok Pesantren Di Wonogiri - Arfiansyah, Mufti Arief (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
The level of Islamic financial literacy is still low compared to the national financial literacy level. One of the government's efforts by promulgating Law Number 18 of 2019 concerning Islamic boarding schools has made Islamic boarding schools have a major role in the development of Islamic finance. Islamic boarding schools are a place to improve Islamic financial literacy and form Islamic financial inclusion. The purpose of this study is to analyze the Effect of Islamic Financial Literacy on Islamic Financial Inclusion in Islamic Boarding Schools in Wonogiri. This study used quantitative methods with data collection using questionnaires analyzed with linear regression analysis methods and assisted by SPSS software. The sample in the study was 158 respondents consisting of kiai, managers, teachers, education staff, and students in 35 Islamic boarding schools in Wonogiri. Research questionnaires have been tested for both validity and reliability. Then the research data has also met the prerequisites for analysis, namely the normality test, linearity test and heteroscedasity test. The results showed that Islamic financial literacy has a positive effect on Islamic financial inclusion in Islamic boarding schools in Wonogiri. Islamic financial literacy has a strong relationship with Islamic financial inclusion in Islamic boarding schools in Wonogiri by 75%. Meanwhile, Islamic financial literacy can affect 56.3% of Islamic financial inclusion. This research shows good financial literacy and will increase the realization of Islamic financial inclusion. The results of this study have an impact on the implementation of education and da'wah in Islamic boarding schools. Islamic boarding schools are not only tasked with organizing Islamic education and Islamic da'wah but also empowering and prospering Islamic boarding schools and communities through providing Islamic financial literacy for all pesantren organizers.